The Employees' Well-Being as a Mediator of Work Stress and Job Insecurity Influences on Health Workers’ Performance During Covid-19 Pandemic Era - Achmad Mohyi; Agus Setia Budi; Nazaruddin Malik; Manah Tarman (International Journal of Applied Business and International Management, 2024)
This study aims to analyze and examine the role of employees' well-being in mediating the effect of work stress and job insecurity on the performance of health workers during the COVID-19 pandemic. This research is explanatory research with data collection methods using survey methods through distributing questionnaires. Respondents in this study were 187 health workers who worked in a hospital in East Java, Indonesia. Data analysis using Partial Least Square. The results showed that work stress had a negative and insignificant effect on the performance of health workers, job insecurity had a negative and significant effect on the performance of health workers, while employees' well-being had a positive and significant effect on the performance of health workers. Job stress has a negative but not significant effect on employees' wellbeing and job insecurity has a negative and significant effect on employees' wellbeing. The results of testing the indirect effect show that employees' well-being is not able to mediate the effect of work stress on the performance of health workers in a negative and insignificant way, while the effect of job insecurity on the performance of health workers employees' well-being is able to mediate negatively and significantly  The conclusion of this research is that work stress, job insecurity, and employees' wellbeing are very important for improving performance.